Effects of metaperiodate and urea solutions on the serological diagnosis of human sporotrichosis using an indirect ELISA test - Coelho, Letícia Maria Leomil (Braz J Microbiol, 2018)
Sporotrichosis is an infection of the skin caused by traumatic inoculation of the fungus Sporothrix schenckii. Definitive diagnosis relies on direct visualization of the fungus or its isolation on culture medium, although both have low sensitivity. Alternatively, the detection of the antibody response offers a more rapid alternative for diagnosis. Although the available immunoassays possess good sensitivity and specificity, cross-reactivity is still a problem. This study aimed to evaluate the effect of sodium metaperiodate and 6 M urea solutions on the serological diagnosis of sporotrichosis using an enzyme-linked immunosorbent assay (ELISA) test. Ninety-six-well plates were sensitized with exoantigens from the yeast phase of S. schenckii. Sera of patients with confirmed sporotrichosis, sera of patients with paracoccidioidomycosis, and sera of individuals with a sporotrichin-negative skin test were tested. Two strategies were used; the first consisted of treating the antigen with sodium metaperiodate solution for different incubation times, and the second consisted of treating the serum with 6 M urea solution for different incubation times. ROC curve analysis revealed that the best discrimination parameters were obtained using 6 M urea solution incubated for 5 min and serum dilution at 1/600. The use of 6 M urea solution improves the performance of the ELISA test in the diagnosis of sporotrichosis.